2000
DOI: 10.3759/tropics.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate Evolution and Extinction on Western and Central Mediterranean Islands.

Abstract: The Mediterranean region, like other biogeographic regions located between continental plates, is rich in islands. Most of them are oceanic-like islands, Le., islands that have been previously connected to the surrounding continents and are faunistically similar, but not identical, to oceanic island (because the island-continent connections occurred in a distant past, were of a short duration, and/or promoted a highly selective and limited faunal transfer). Insular (Le., non-continental) vertebrate faunas are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Storm petrel populations are stable at the few long-term monitored sites [282], but many suitable breeding sites have been destroyed since historical times along coastlines. Paleontological records confirm that the distribution of many species was much larger, even occupying habitats in the interior of large islands relatively far from the sea, where recolonization is now impossible [283]. Population recoveries of Mediterranean seabirds must be considered only partial, and only occurring where protection is effective [284].…”
Section: Resultsmentioning
confidence: 99%
“…Storm petrel populations are stable at the few long-term monitored sites [282], but many suitable breeding sites have been destroyed since historical times along coastlines. Paleontological records confirm that the distribution of many species was much larger, even occupying habitats in the interior of large islands relatively far from the sea, where recolonization is now impossible [283]. Population recoveries of Mediterranean seabirds must be considered only partial, and only occurring where protection is effective [284].…”
Section: Resultsmentioning
confidence: 99%
“…Interpretation of the insular vertebrate evolution and analysis of the extinction patterns on the western Mediterranean islands has suggested that land connections between all Balearic islands were present during the Messinian salinity crisis (Hsu, Ryan & Cita, 1973)) between 5.7 and 5.35 Mya (Gautier et al, 1994). Also, connections between the islands and the surrounding continental land have been envisaged (Alcover, 1999). The floristic relationships between the Pytiusic islands and the Iberian Peninsula (especially with its eastern zone) are supported by the shared presence of several narrowly distributed species in common, many of them being absent from the eastern Balearics, as evidenced by Font Quer (1927).…”
Section: Systematic Positionmentioning
confidence: 98%
“…During the late Middle Pleistocene, Hippopotamus melitensis inhabited Malta, the smallest of Mediterranean islands on which hippopotami were present (Alcover, 2000;Caloi et al, 1986;Herridge, 2010;Marra, 2005a;Savona-Ventura and Mifsud, 1998). Its body mass was approximately 900 kg (Lomolino et al, 2013) and displayed a variation in body size exceeding that of a mainland population (Van der Geer et al, 2010).…”
Section: Pleistocene Mediterranean Hippopotamimentioning
confidence: 99%